Sociodemographic and behavioural differences between frequent and non-frequent users of convenience food in Germany - Dittmann, Anna; Werner, Lea; Hörz, Lena; Luft, Theresa; Finkbeiner, Fiona; Storcksdieck genannt Bonsmann, Stefan (Frontiers in Nutrition, 2024)
Convenience foods are a double-edged sword in that they provide quick and easy nutrition but may promote non-communicable diseases related to excess intakes of sugar, fat, and salt. To inform the German national reduction and innovation strategy for less sugar, fat, and salt in processed foods, the present study sought to analyse the consumption frequency of selected convenience foods and to determine sociodemographic and behavioural factors that characterise frequent users.In a representative computer-assisted telephone interview survey in the adult German population (N=3997) conducted in 2018, consumption frequency of 21 convenience foods was assessed. To characterise frequent in contrast to non-frequent users, data on sociodemographics and behavioural aspects were compared. Statistical analyses comprised Chi-square tests with Bonferroni correction as well as Spearman's rank correlation. Cramer's V was used to determine the strength of an association.Results: Overall and among frequent users (7.7% of the sample) sweet convenience foods and savoury cooking aids were consumed most frequently. Around 75% of the participants indicated little-to-no consumption of 19 of the 21 convenience foods. Male gender (p<0.001), younger age (p<0.001), and not having a high level of education (p=0.017) were identified as key characteristics of frequent users. Furthermore, frequent users were more likely than non-frequent users to live in a family household (p=0.003) or without a partner (p<0.001), and to work in shifts (p=0.002). Additionally, they showed significantly lower cooking skills (p<0.001).Conclusion: Public health interventions to limit excess intakes of sugar, fat, and salt from convenience food in Germany should target people of male gender, younger age, and having a lower level of education. On the behavioural side, developing the skills to cook from scratch emerged as major point of focus. Simultaneously, reformulation of the food offer should continue in order to help transition to a more health-promoting food environment.